One-year prevalence and the association between SARS-CoV-2 cycle threshold, comorbidity and outcomes in population of Babol, North of Iran (2020-2021). - Mehrdad Halaji; Abazar Pournajaf; Farzin Sadeghi; Ali Hasanzadeh; Mohammad Chehrazi; Hemmat Gholinia; Fatemeh Hejazi Amiri; Saghar Saber Amoli; Mostafa Javanian; Masoumeh Bayani; Mahmoud Sadeghi Haddad Zavareh; Mehran Shokri; et al. (Babol University of Medical Sciences, 2022)
Background: The present study aimed to investigate the one-year prevalence of SARS-CoV-2, common comorbidities and demographic information among negative- and positive rRT-PCR in health care workers (HCW), hospitalized and outpatients. Also, the association between SARS-CoV-2 cycle threshold (Ct) and the outcomes of patients were analyzed in Babol, northern Iran. Methods: This large retrospective cross-sectional study was performed between March 2020 and March 2021. The records of 19232 hospitalized, outpatients and HCW suspected to COVID-19 were collected from teaching hospitals in the North of Iran. Results: Out of the 19232 suspected to COVID-19 patients, 7251 (37.7%) had a positive rRT-PCR result; 652 (9%), 4599 (63.4%) and 2000 (27.6%) of those were categorized as HCW, hospitalized and outpatients, respectively. Moreover, between the hospitalized and the outpatient group, 10.2 and 0.8% cases died, whereas no death cases were reported in the HCW. Furthermore, it seems that death rate was significantly different between the three groups of Ct value, the highest mortality in those with Ct between 21 and 30 (group B=7.6%) and the lowest in the group with the highest Ct (between 31 and 40 = 5.5%) (p<0.001). Conclusion: In summary, 37.7% of cases were positive for SARS-CoV-2; of which, 63.4, 27.6 and 9% were hospitalized, outpatients and HCW, respectively. With regard to the mortality rate in hospitalized patients and the significant association with Ct under 20 and 30, it seems that the early detection and the initial quantification of SARS-CoV-2 in the first week of the conflict and therapeutic considerations to reduce the relative load can reduce the mortality rate.